Thermodynamic analysis of concentrated solar energy layouts integrated with combined power system - Bergantini Botamede, Bernardo [UNESP]; Oliveira Salviano, Leandro [UNESP] (Elsevier, 2023)
Solar Thermal Energy is currently used for power generation as a reliable carbon-free source in many countries. Unfortunately, none commercial project under operation is verified in Brazil although a great solar potential is verified. In this context, an interesting strategy to transition is to develop a hybrid solar plant that can be applied to current thermoelectric power plants. Therefore, the present work investigates several layout alternatives for coupling a solar thermal plant with an operational plant based on a combined cycle (Brayton and Rankine cycle) located in Brazil. A parabolic trough collector was selected for this study, considering oil and molten salt as working fluids. The thermodynamic modeling and additional mathematical models were developed on the open-source software OpenModelica. The thermodynamic modeling of the current power plant model was validated through real operating data, kindly provided by a private company. Moreover, a typical concentrate solar plant with thermal storage was modeled and validated through reference software called System Advisor Model (SAM) from National Renewable Energy Laboratory (NREL). A proposed solar plant with thermal storage is integrated into the Heat Recovery Steam Generator (HRSG) considering six layouts with synthetic oil and six layouts with molten salt as working fluid on the solar field, where the solar plant is used either to preheat water, to evaporate steam, to superheat steam, or a combination of these processes in parallel with the HRSG. Results showed the layouts that use solar energy to superheat saturated steam taken from the drum, in a parallel configuration to the HRSG superheaters, have the best thermodynamic performance, with solar-to-electric conversion efficiency up to 32.29 %, and increases of 1.46 % in average daily steam turbine power under nominal Direct Normal Irradiance (DNI) conditions. Moreover, it was evaluated that on an annual basis the hybrid powerplant has the potential to avoid fossil fuel consumption up to 34,410 MMBtu, representing up to 1,997 ton CO2 emissions avoidance and up to US$ 458,682.52 fuel cost savings.
Keywords: Concentrated solar power (CSP); Integrated solar combined cycle (ISCC); OpenModelica; Parabolic trough collector; Power plant; Thermodynamic modeling